The effect of cryogenic treatment on dry sliding wear mechanisms in hard coatings - Kurşuncu, Bilal; Kurşuncu, Bilal (Emerald Group Publishing Ltd, 2021)
Purpose - The effect of cryogenic heat treatment on the mechanical properties of different materials has been frequently investigated by researchers in recent years. The purpose of this paper is to investigate wear behaviour of monolayer, multilayer and nanocomposite coatings after cryogenic heat treatment. It is a first in its field in terms of both the heat treatment used and the coatings examined. Design/methodology/approach - The aCN/TiAlN, TiAlN and ncTiAlSiN hard coatings deposited on the AISI D2 steel substrate were subjected to cryogenic heat treatment at -145(o)C and -196(o)C for 24 h and then tempered at 200(o)C for 2 h. Then, the samples were subjected to wear tests of 5, 10 and 15 N three different load values. The wear mechanisms occurring on the wear surfaces were determined by scanning electron microscope supported by EDS. Findings - Oxidation, fatigue and delamination wear mechanisms were realized on the surfaces of the samples subjected to dry sliding wear test. The wear resistance of S1 increased with cryogenic heat treatment. According to the wear test results of the untreated samples, it was found that the samples with lower hardness than the others had higher wear resistance. The wear resistance of S1 and S2 samples was increased by cryogenic heat treatment. The best wear resistance in all parameters was obtained by S1. Oxidation in the S1 was found to have a positive effect on wear resistance. According to EDS results after wear of S2, chromium-rich layer was found on the surface of the material. It is understood that cryogenic heat treatment causes carbide precipitation in the inner structure of the substrate material. Originality/value - The effect of cryogenic heat treatment on the mechanical properties of different materials has been frequently investigated by researchers in recent years. In this study, wear behaviour of monolayer, multilayer and nanocomposite coatings after cryogenic heat treatment was investigated. It is a first in its field in terms of both the heat treatment used and the coatings examined. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-03-2020-0111/
Keywords: Dry Sliding Wear; Dlc Coating; Nanocomposite Hard Coating; Cryogenic Treatment; Wear Mechanism; Nano-Layer Coating